In-situ microfibrilization of liquid metal droplets in polymer matrix for enhancing electromagnetic interference shielding and thermal conductivity - Huang, Ming-Lu; Luo, Cheng-Long; Sun, Chang; Zhao, Kun-Yan; Wang, Ming (Composites science and technology, 2024)
Herein, liquid metal microfibers (LMM) were constructed in poly (ε-caprolactone) (PCL) matrix and PCL/carbon nanotubes (CNT) composites via an in-situ microfibrilization of liquid metal (LM) droplets by a layer-by-layer stacking method. The aspect ratios of LMMs in the composites can be easily adjusted by controlling the number layers. The effect of LMM aspect ratios on electromagnetic interference (EMI) shielding effectiveness (SE) and thermal conductivity is discussed. The results show that the EMI SE value and the thermal conductivity increase with increasing aspect ratios of LMMs. In addition, the EMI shielding mechanism of PCL/LMM and PCL/LMM/CNT composites is evaluated comprehensively through the combination of electromagnetic simulation and experimental investigation. The efficiently conductive network can be formed in the composites with LMMs, which enhance EMI SE and thermal conductivity. Furthermore, the electric field distribution on the LMM surface is uneven, which enhances the polarization loss ability to electromagnetic waves. [Display omitted] •Liquid metal microfibers are constructed in polymer matrix.•Liquid metal microfibers can enhance EMI shielding abruptly.•Thermal conductivity increases with aspect ratios of the microfibers.•The uneven distribution of electric field enhance interface polarization.